Treatment of Palm Oil Mill Effluent in Microbial Fuel Cell Using Polyacrylonitrile Carbon Felt as Electrode - Khan, Maksudur R.; E., Baranitharan; D. M. R., Prasad (Engineering and Technology Publishing, 2013)
Palm oil mill effluent (POME) is an organic waste material produced at the oil palm mills. It is highly polluting due to its high content of biological and chemical oxygen demand. In the present paper, POME was treated using double chamber microbial fuel cell with simultaneous generation of electricity. Polyacrylonitrile carbon felt (PACF) was used as electrode and anaerobic sludge was used as inoculum throughout the MFC experiments. Various dilutions of raw POME were used to analyze the MFC power generation, COD removal efficiency and coulombic efficiency. Among the raw POME and different concentrations of POME used, the PACF with raw POME showed the maximum power density and volumetric power density of about 45mW/m2 and 304mW/m3 respectively but it showed low coulombic efficiency and low COD removal efficiency of about 0.8% and 45% respectively while PACF with 1:50 dilution showed higher COD removal efficiency and coulombic efficiency of about 70% and 24% but showed low power density and low volumetric power density of about 22mW/m2 and 149mW/m3 respectively. The results show that MFC possesses great potential for the simultaneous treatment of POME and power generation using PACF as electrode.